Labour dismissal action, applicable law and qualification issue linked to the prescription: for the purpose of Judgment nº 300/2020 of the Superior Court of Justice of Madrid, Labour Chamber - Álvarez Agoués, Laura (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The judicial resolution that is the subject of this comment satisfactorily resolves three key issues related to the scope of the International Private Law: the qualification of the statute of limitations, the determination of the law applicable to a lawsuit of a labor nature with a cross-border dimension and finally, the interaction between the normative blocks that come into play in the litigation case. In particular, the resolution discards the procedural qualification of the prescription and derives from it the application of the Lex Contractus (Dominican Law) to it. In any case, the absence of any reference to the conflict rule applicable to litigation, such as the Rome I Regulation on the law applicable to contractual obligations, is surprising.